Features of Renewal in the Poetry of Abi Al-Qasim Saad Allah Through His Book "Rebel and Love" - Kehiha, Abdelhamid (Journal of Human Sciences, 2023)
Poetry is a living means for establishing identity and defending patriotism, and because every revolution must have a poet who carries its message and keeps pace with its actions and developments. The Algerian poet Abu al-Qasim Saadallah was one of the sons of the revolution who harnessed their pens; In order to defend the revolution, and to urge the people to continue the struggle with the aim of independence, and the restoration of national sovereignty, which is a mass demand that cannot be disputed or waived and the legitimate right of the Algerian nation, and his poems often reflected that patriotism and revolutionary spirit that we find in his poetic language, poetic imagery and rhythm The musician, the most creative of its paintings and its truest images, as he created paintings of the utmost beauty, which paved the way for him to renew the artistic form of the Algerian poem.